2001
DOI: 10.1038/nn759
|View full text |Cite
|
Sign up to set email alerts
|

Human memory formation is accompanied by rhinal–hippocampal coupling and decoupling

Abstract: In humans, distinct processes within the hippocampus and rhinal cortex support declarative memory formation. But do these medial temporal lobe (MTL) substructures directly cooperate in encoding new memories? Phase synchronization of gamma-band electroencephalogram (EEG) oscillations (around 40 Hz) is a general mechanism of transiently connecting neural assemblies. We recorded depth-EEG from within the MTL of epilepsy patients performing a memorization task. Successful as opposed to unsuccessful memory formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
416
5
13

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 658 publications
(475 citation statements)
references
References 44 publications
41
416
5
13
Order By: Relevance
“…Indeed, subdural ECoG recordings have demonstrated event-related gamma activity in topographic and temporal patterns that are consistent with the functional anatomy and processing dynamics of sensorimotor, auditory, visual, and language function (Crone et al, 2006), oculomotor function (Lachaux et al, 2006) and memory (Fell et al, 2001;Howard et al, 2003;Sederberg et al 2003;Mainy et al, 2007). From the perspective of ECoG, this gamma response is not limited to a single gamma band, e.g.…”
Section: Discussionmentioning
confidence: 58%
“…Indeed, subdural ECoG recordings have demonstrated event-related gamma activity in topographic and temporal patterns that are consistent with the functional anatomy and processing dynamics of sensorimotor, auditory, visual, and language function (Crone et al, 2006), oculomotor function (Lachaux et al, 2006) and memory (Fell et al, 2001;Howard et al, 2003;Sederberg et al 2003;Mainy et al, 2007). From the perspective of ECoG, this gamma response is not limited to a single gamma band, e.g.…”
Section: Discussionmentioning
confidence: 58%
“…Gamma-band synchronization is observed during visual (Hoogenboom et al, 2006;Muthukumaraswamy et al, 2009), somatosensory (Bauer et al, 2006), and auditory (Brosch et al, 2002) stimulation; it is involved in memory processes (Fell et al, 2001;Howard et al, 2003) and motor control (Brown et al, 1998;Schoffelen et al, 2005). It is enhanced during attention (Fries et al, 2001;Bosman et al, 2012), and its moment-by-moment fluctuations predict the behavioral benefits of attention (Womelsdorf et al, 2006;Hoogenboom et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recent iEEG studies have put a strong emphasis on gamma band activations in particular, in association with a wide range of cognitive processes, including memory (Fell et al, 2001;Howard et al, 2003;Mainy et al, 2007), visual attention and perception (Brovelli et al, 2005;Lachaux et al, 2000Lachaux et al, , 2005Tallon-Baudry et al, 2005;Tanji et al, 2005), audition (Bidet-Caulet et al, 2003;Edwards et al, 2005), somatosensory and motor processes Crone, Sinai and Korzeniewska, 2006;Lachaux et al, 2005;Aoki et al, 1999;Pfurtscheller et al, 2003;Szurhaj et al, 2005), and language . Importantly, in all those studies, gamma band activity was observed only in very specific brain regions, dependant on the tasks, and in good agreement with the functional networks revealed by fMRI .…”
Section: Introductionmentioning
confidence: 99%